Energy use and emissions of two stroke powered tricycles in Metro Manila by instantaneous emissions modeling - Biona, Jose Bienvenido Manuel M. (Animo Repository, 2007)
The fuel consumption CO, CO2, NOx and HC emission factors of two stroke-powered tricycles in Metro Manila were determined and compared using an instantaneous emissions model. Results show that fuel consumption and HC emissions in middle class residential areas and main roads are similar but lower than levels in low income residential areas. On the average, tricycles in Metro Manila consume 24.41 km/l of fuel and produces 9.5, 9.7, 40.5 and 0.07 g/km of HC, CO, CO2 and NOx, respectively. They fail to satisfy HC, CO and NOx emission limits set by reference standards in the Philippines and other Asian countries. They produce greater HC and CO emissions than gasoline fueled private cars and diesel powered public jeepneys, taxis and buses on a per passenger-km basis but significantly lower NOx emissions. Tricycles account for 15.4% of the total HC emissions from mobile sources in the metropolis while their contributions to CO, CO2 and NOx are minimal. The model adopted and results provide a basis for formulating better environmental strategies to effectively reduce tricycle emissions and improve air quality in Metro Manila and other cities.